Italian Political Cinema Figures of the Long '68 - Resmini, Mauro (University of Minnesota Press, 2023)
An exploration of how film has made legible the Italian long '68 as a moment of crisis and transitionTraditionally, the definition of political cinema assumes a relationship between cinema and politics. In contrast to this view, author Mauro Resmini sees this relationship as an impasse. To illustrate this theory, Resmini turns to Italian cinema to explore how films have reinvented the link between popular art and radical politics in Italy from 1968 to the early 1980s, a period of intense political and cultural struggles also known as the long '68.Italian Political Cinema conjures a multifaceted, complex portrayal of Italian society. Centered on emblematic figures in Italian cinema, it maps the currents of antagonism and repression that defined this period in the country's history. Resmini explores how film imagined the possibilities, obstacles, and pitfalls that characterized the Italian long '68 as a moment of crisis and transition. From workerism to autonomist Marxism to feminism, this book further expands the debate on political cinema with a critical interpretation of influential texts, some of which are currently only available in Italian.A comprehensive and novel redefinition of political film, Italian Political Cinema introduces its audience to lesser-known directors alongside greats such as Pasolini, Bertolucci, Antonioni, and Bellocchio. Resmini offers access to untranslated work in Italian philosophy, political theory, and film theory, and forcefully advocates for the continued artistic and political relevance of these films in our time.